Desenvolvimento inicial de seleções de lima ácida tahiti em diferentes porta-enxertos sob condições irrigadas e não irrigadas - Oliveira, Rebeca Espíndola de (Universidade Federal de São Carlos, 2021)
Brazil is one of the largest citrus producers in the world and is a major producer of limes and lemons, especially the production of Tahiti acid lime. The Brazilian citrus industry represents great economic and social importance and the selection of new materials, both varieties and rootstocks, such as dwarfing rootstocks, have allowed the implantation Higher planting densitie , allowing productivity gains in citrus orchards. Furthermore, the use of irrigation generates a series of benefits to production, affecting both the characteristics of vegetative development and reproductive stage of the plant. Thus, the objective of this work was to evaluate the initial development of different Tahiti lime scion/rootstock combinations under different drip irrigation management and dryland farming. For this, in March 2020, seedlings of Tahiti acid lime of five different combinations scion/rootstock were planted and submitted to two irrigation treatments and one dryland farming. The experimental design was in randomized blocks in a split-plot scheme. The diameter of rootstock , height, canopy volume, canopy diameter, Coverage Rate in the tree-Row (TCCL), Coverage Rate in the tree Inter- row (TCCE) and Vegetative Vigor Index were evaluated ( IVV), as well as the growth of plants during the first year after planting. The results were submitted to analysis of variance (ANOVA) and the Scott-Knott test (5%). From the statistical analysis, it was possible to verify that the combinations BRS Ponta Firme/FD and IAC 10/152 presented the highest plant height values, diameter of scion, volume of scion, TCCE, TCCL and IVV, compared to the others. The H228, H14 citrandarin and the Flying Dragon trifoliate, when grafted with the IAC 10 canopy, induced the formation of smaller plants, with smaller canopy volume and less vigor. There was no significant difference between the irrigated and non-irrigated treatments, however it was possible to observe some differences in height growth over time. For some scion/rootstock combinations, both management of irrigation resulted in greater height, compared to the non-irrigated treatment, indicating the rootstocks with greater response to irrigation management.
Initial development of Tahiti acid lime selections on different rootstocks under irrigated and non-irrigated conditions
Keywords: Citricultura; Gotejamento; Crescimento vegetativo; Citriculture; Drip system; Vegetative growth; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA